THE IMPLEMENTATION OF TRANSITION-ACTION-DETAILS STRATEGY TO IMPROVE THE STUDENTS’ WRITING ABILITY IN RECOUNT TEXT - Muhalim Muhalim (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2015)
This research aimed to explain the improvement of the students’ writing ability and the students’ response through the implementation of “Transition-Action-Details” strategy in teaching writing. The researcher used a classroom action research principle to collect the data that consisted of two cycles. Each cycle consisted of four meetings. The findings of the research were the improvement of students’ writing ability in cycle I to  cycle II was 12.2%, and the other side, students’ participation or activeness at cycle I in the 1st meeting was 45%, 2nd meeting 59%, 3rd meeting was 63% and 4th meeting was 73 %. So the average score was 60%. Where in cycle II, in the 1st meeting was 67%, 2nd meeting was 72%, 3rd meeting was 68% and 4th meeting was 78%. There is a significant score in the average score (71.87%). Based on the average score above, it had improvement from cycle I to cycle II (11.64 %).